The arts : a visual encyclopedia - Hodge, Susie, 1960-; Taylor, David, 1969 April 13-; Fullman, Joe; Chrisp, Peter (DK Publishing, 2017)
"Full of stunning images and amazing facts, The Arts: a Visual Encyclopedia is the essential guide to painting, sculpture, photography, music, and dance."--Back cover.